Exploring the consistency and value of humour style profiles. Issue 1 (2nd January 2020) - Evans, Thomas Rhys; Johannes, Niklas; Winska, Joanna; Glinksa-Newes, Aldona; van Stekelenburg, Aart; Nilsonne, Gustav; Dean, Laura; Fido, Dean; Galloway, Graeme; Jones, Sian; Masson, Isla; Soares, Andre; et al.
ABSTRACT: Establishing generalisable humour style profiles promises to have significant value for educational, clinical, and occupational application. However, previous research investigating such profiles has thus far presented inconsistent results. To determine the generalisability and value of humour style profiles, a large and geographically diverse examination of humour styles was conducted through a cross-sectional questionnaire methodology involving 863 participants from across three world regions. Findings identify inconsistencies in the humour style profiles across countries tested and the extant literature, possibly indicative of cultural differences in the behavioural expression of trait humour. Furthermore, when directly compared, humour types, rather than humour styles, consistently provide the greatest predictive value for friendship and well-being outcomes. As such, with respect to both consistency and value, capturing humour style profiles appears to represent a relatively reductionist approach to appreciating the nuances in the use and consequences of humour.